Giant Hydronephrosis Due to Congenital Uretropelvic Junction Obstruction, a Report of 2 cases - Sadeghi-Bojd, Simin; Fazeli, Faramarz; keshavarz, kambiz; Baktash, Maryam (Journal of Pediatric Nephrology, 2014)
Ureteropelvic junction (UPJ) stenosis occurs in 13% of children. Antenatally, the diagnosis is possible by showing renal pelvis dilatation by obstetric ultrasonography. Giant hydronephrosis (GH) is a rare condition. There are different etiologies for GH which are mostly congenital and occur during infancy and childhood. GH was confirmed by complementary evaluations in a 2-month-old female infant with poor feeding, lethargy, and vomiting together with an antenatal sonography in favor of hydronephrosis, and a 5-year-old boy with an abdominal mass diagnosed by sonography following 2 weeks of progressive abdominal distention. Pyeloplasty was associated with an excellent result in both of them. Keywords: Hydronephrosis; Ureteral Obstruction; Congenital; Urologic Diseases.